2014
DOI: 10.1097/mlr.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Unique Device Identification in Electronic Health Record Systems

Abstract: We provide recommendations for regulations, organizational sharing, and professional society engagement to raise awareness of and overcome UDI system implementation challenges. Implementation of the UDI system will require integration of people, process, and technology to achieve benefits envisioned by FDA, including improved postmarket device surveillance and quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Registries are critically important for uniquely identifying devices, as almost none of the nation's electronic health records at this time can automatically uniquely identify a device and link it to the outcome data of individual patients 27 . Similarly, very limited national data exist that can be used to identify medical devices and link them to patient outcomes within claim systems 27 . Large U.S. and international registries might be very attractive in this context and potentially could meet the needs of the FDA and regulators worldwide.…”
Section: Other Icor Studies Of Devices and Outcomesmentioning
confidence: 99%
“…Registries are critically important for uniquely identifying devices, as almost none of the nation's electronic health records at this time can automatically uniquely identify a device and link it to the outcome data of individual patients 27 . Similarly, very limited national data exist that can be used to identify medical devices and link them to patient outcomes within claim systems 27 . Large U.S. and international registries might be very attractive in this context and potentially could meet the needs of the FDA and regulators worldwide.…”
Section: Other Icor Studies Of Devices and Outcomesmentioning
confidence: 99%
“…The objective of the reported study was to understand the experiences of health systems that had implemented UDI at the POC in order to develop a set of practical recommendations for health system implementation, building on prior work [18][19][20] and advancing the field. Implantable devices were the focus because they are higher risk, discussion of all devices would impact the level of detail possible in interviews, and a roadmap for higher risk devices could serve as a model for broad UDI implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Technology can increase quality if used wisely for education and training, has a very important meaning for well-being. The results showed that technology-based instructional greatly helped students understand instruction [40]. Instructional online has become an acceptable part and is even expected to facilitate a more effective instructional [42].…”
Section: Introductionmentioning
confidence: 96%